Faster reduction in hyperinflation and improvement in lung ventilation inhomogeneity promoted by aclidinium compared to glycopyrronium in severe stable COPD patients. A randomized crossover study. (December 2015) - Santus, Pierachille; Radovanovic, Dejan; Di Marco, Fabiano; Raccanelli, Rita; Valenti, Vincenzo; Centanni, Stefano
Abstract: Standard spyrometric assessment in chronic obstructive pulmonary disease (COPD) only evaluates bronchial obstruction. However, airflow limitation and hyperinflation are the main pathophysiological factors responsible for dyspnoea and reduced exercise tolerance in patients with COPD. This study evaluated the effects of aclidinium bromide 400 μg and glycopyrronium bromide 50 μg on these parameters. Patients with stable severe/very severe COPD were randomized in this double-blind, double-dummy, crossover, Phase IV study. Patients received single doses of each drug on separate days. Primary endpoints were changes in residual volume (RV) and intra-thoracic gas volume (ITGV), assessed by full-body plethysmography. Other endpoints included changes variations in lung ventilation inhomogeneity (Phase III slope of single-breath nitrogen washout test, SBN2), dyspnoea visual analogue scale, and pulmonary specific total airway resistances. Assessments were performed at baseline and 5, 15, 30, 60, and 180 min post-administration. Thirty-seven patients were randomized (31 male; mean age 71 years). Aclidinium and glycopyrronium significantly improved ITGV versus baseline at all-time points (p < 0.05). Significant improvements in RV were observed after 5 min with aclidinium and after 60 min with glycopyrronium. RV improvements were significantly greater with aclidinium than glycopyrronium from 5 to 60 min post-administration (p < 0.05). Both treatments improved dyspnoea versus baseline at all-time points (p < 0.05). Aclidinium significantly improved ventilation inhomogeneity versus baseline at all-time points; no significant changes were observed for glycopyrronium. For the first time two long-acting muscarinic antagonists have been compared in acute conditions with body plethysmography and SBN2 test. We demonstrated that both aclidinium and glycopyrronium significantly reduce hyperinflation and dyspnoea in severe and very severe COPD patients. Aclidinium however promoted a faster reduction in RV and was the only able to reduce lung ventilation inhomogeneity. Trial Registration numbers available on Clinicaltrials.gov:NCT02181023 .